Comparison of clinical presentations and burden of respiratory syncytial virus in infants across three distinct healthcare settings in Davidson County, Tennessee. (July 2022) - Rankin, Danielle A.; Haddadin, Zaid; Lipworth, Loren; Stahl, Anna L.; Fryzek, Jon; Suh, Mina; Shepard, Donald S.; Varjabedian, Rebekkah; Fernandez, Kailee N.; Salib, Seifein; Villarreal, Jessica; Bruce, Mercedes; et al.
Background: The burden of respiratory syncytial virus (RSV)-associated acute respiratory illnesses among healthy infants (<1 year) in the inpatient setting is well established. The focus on RSV-associated illnesses in the outpatient (OP) and emergency department (ED) settings are however understudied. We sought to determine the spectrum of RSV illnesses in infants at three distinct healthcare settings. Methods: From 16 December 2019 through 30 April 2020, we performed an active, prospective RSV surveillance study among infants seeking medical attention from an inpatient (IP), ED, or OP clinic. Infants were eligible if they presented with fever and/or respiratory symptoms. Demographics, clinical characteristics, and illness histories were collected during parental/guardian interviews, followed by a medical chart review and illness follow-up surveys. Research nasal swabs were collected and tested for respiratory pathogens for all enrolled infants. Results: Of the 627 infants screened, 475 were confirmed eligible; 360 were enrolled and research tested. Within this final cohort, 101 (28%) were RSV-positive (IP = 37, ED = 18, and OP = 46). Of the RSV-positive infants, the median age was 4.5 months and 57% had ⩾2 healthcare encounters. The majority of RSV-positive infants were not born premature (88%) nor had underlying medical conditions (92%). RSV-positive infants, however, were more likely to have a lower respiratory tract infection than RSV-negative infants (76% vs 39%, p  < 0.001). Hospitalized infants with RSV were younger, 65% required supplemental oxygen, were more likely to have lower respiratory tract symptoms, and more often had shortness of breath and rales/rhonchi than RSV-positive infants in the ED and OP setting. Conclusion: Infants with RSV illnesses seek healthcare for multiple encounters in various settings and have clinical difference across settings. Prevention measures, especially targeted toward healthy, young infants are needed to effectively reduce RSV-associated healthcare visits.